Tubal choriocarcinoma: a rare entity - Sah, Shanti; Kaira, Vaanika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Choriocarcinoma is common after molar pregnancy and follows in almost 50% of such pregnancies, but in some rare cases it follows even after an ectopic pregnancy. Tubal choricarcinoma associated with an ectopic pregnancy has an aggressive course but it is curable.